Proximate composition, amino acids, and fatty acids contents of dried shrimp products available in Jashore region, Bangladesh (Asian Journal of Medical and Biological Research, 2021)
Dried shrimp has some special advantageous such as long shelf-life, high nutritional content, and ease of transportation considered as a healthy choice of food. The nutritional properties of three common and demandable dried shrimp species available in Jashore, Bangladesh were evaluated. The moisture content of dried Palaemon karnafuliensis, Metapenaeus Monoceros and Ferapenaeus indicus was determined 19.7±0.40%, 20.5±0.25% and 24.9±0.21%, respectively. The protein content was found 57.46±5.88%, 62.5±1.98%, and 55.5±1.85% in Palaemon karnafuliensis, Metapenaeus Monoceros, and Ferapenaeus indicus, respectively. The ash and fat content of Palaemon karnafuliensis, Metapenaeus Monoceros and Ferapenaeus indicus were observed 12.20±0.90% and 1.90±0.15%, 10.20±0.39% and 1.48±0.32%, 8.57±1.43%, and 1.08±0.21%, respectively. Total saturated fatty acids content was found 31.56%, 29.21%, 38.59 in Palaemon karnafuliensis, Metapenaeus monoceros, and Ferapenaeus indicus, respectively. The polyunsaturated fatty acids was found 42.60%, 42.29%, and 37.80% in Palaemon karnafuliensis, Metapenaeus monoceros, and Ferapenaeus indicus, respectively. There were nine non-essential and eight essential amino acids found in the dried shrimp products. Glutamine, proline, glycine and alanine were dominated among the non-essential amino acid. Lysine was found a significant amount in the study. All the three dried shrimp products were considered as highly nutritive and less fat value which is considered healthy for the consumers.Asian J. Med. Biol. Res. 2021, 7 (2), 138-146